1994
DOI: 10.1227/00006123-199402000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hypertensive Cerebellar Hemorrhage–Surgical or Conservative Management?

Abstract: One hundred and one consecutive patients with hypertensive cerebellar hemorrhage were analyzed to determine the criteria for surgery. New criteria based on the patient's Glasgow Coma Scale score at admission and the maximum diameter of the hematoma, as disclosed by computed tomography, are proposed from a retrospective analysis of 52 earlier cases. The criteria are as follows: 1) patients with Glasgow Coma Scale scores of 14 or 15 and with a hematoma of less than 40 mm in maximum diameter are treated conservat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
45
0
26

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(77 citation statements)
references
References 9 publications
6
45
0
26
Order By: Relevance
“…These results support previous reports, such as those by Kobayashi et al [13]in a relatively large series of 101 patients using the size of the haematoma and the neurological status on admission as guidelines.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results support previous reports, such as those by Kobayashi et al [13]in a relatively large series of 101 patients using the size of the haematoma and the neurological status on admission as guidelines.…”
Section: Discussionsupporting
confidence: 92%
“…tumours), the presence of signs indicative of brainstem compression or neurological deterioration. These results correlate well with those of Kobayashi et al [13]who found in their large series that patients with a GCS between 13 and 15 and a haematoma size <4 cm had a good outcome with a conservative treatment. Other reports [7, 9, 14, 15, 16]also indicate that a haematoma size of less than 3 cm should be treated conservatively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The surgical treatment options include craniotomy, stereotactic thrombolysis and/or aspiration, endoscopic lysis and/or aspiration, ventriculostomy and decompressed craniotomy or combination of the above-mentioned procedures. Until now, it was reported that patients with good neurological status (according to GCS with score of 14 or more) and with small hemorrhage (volume of the hematoma less than 40 ml) stand better chances for a full recovery or presence of minor invalidity during the conduction of the conservative treatment (20). Early craniotomy, on the other hand, is recommended for patients with cerebellar hematoma as the degree of neurological deterioration after cerebellar hemorrhage is very high and unpredictable.…”
Section: Discussionmentioning
confidence: 99%